AN ANALYSIS OF NARRATIVE FUNCTION AND CHARACTER BASED ON VLADIMIR PROPP THEORY IN THE DINOSAUR MOVIE - Shafina Syafadevrianti Fajrin; Indah Lestari (Universitas Gunadarma, 2023)
Narration is a story that tells about actions that occur from beginning to end. This research analyzed narrative functions and character analysis or sphere of action by using Vladimir Propp's Theory. The purpose of this research is to explain narrative functions and sphere of actions by Vladimir Propp's theory in The Dinosaur movie and it is useful to be a reference to find out how to apply the theory in research, especially in analyzing 31 (thirty-one) of narrative functions and sphere of actions. This research used the qualitative method. The result of this research, the researcher found 13 (thirteen) out of 31 (thirty-one) narrative functions there is pursuit (1 data), departure (1 data), the first function of the donor (1 data), rescue (1 data), violatio n (1 data), difficult task (1 data), reconnaissance (1 data), beginning counteraction (1 data), unrecognized arrival (1 data), interdiction (1 data), exposure (1 data), victory (1 data) and the hero’s reaction (1 data). Also for the sphere of action, the researcher found 4 (four) out of 7 (seven) there are villain (1 data), helper (1 data), hero (1 data), and false hero (1 data).